2017
DOI: 10.1038/s41598-017-09148-7
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal transcription is regulated by PGC-1alpha and disturbed in Huntington’s disease

Abstract: PGC-1α is a versatile inducer of mitochondrial biogenesis and responsive to the changing energy demands of the cell. As mitochondrial ATP production requires proteins that derive from translation products of cytosolic ribosomes, we asked whether PGC-1α directly takes part in ribosomal biogenesis. Here, we show that a fraction of cellular PGC-1α localizes to the nucleolus, the site of ribosomal transcription by RNA polymerase I. Upon activation PGC-1α associates with the ribosomal DNA and boosts recruitment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…As expected, and through the enrichment analysis, PPARGC1A was found to be associated with the regulation of progesterone synthesized in the biosynthetic pathway ( Supplementary Figure S1B). The deregulation of transcription and mitochondrial function caused by PPARGC1A is associated with conditions such as amyotrophic lateral sclerosis, Parkinson's disease, Alzheimer's disease, and Huntington's disease (Weydt et al, 2006;Eschbach et al, 2013;Jesse et al, 2017). Additionally, the second H-B, CTBP1 plays a role in the regulation of gene expression during embryonic development, as well as participation in axial patterning and cellular proliferation and differentiation (Hildebrand and Soriano, 2002;Van Hateren et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, and through the enrichment analysis, PPARGC1A was found to be associated with the regulation of progesterone synthesized in the biosynthetic pathway ( Supplementary Figure S1B). The deregulation of transcription and mitochondrial function caused by PPARGC1A is associated with conditions such as amyotrophic lateral sclerosis, Parkinson's disease, Alzheimer's disease, and Huntington's disease (Weydt et al, 2006;Eschbach et al, 2013;Jesse et al, 2017). Additionally, the second H-B, CTBP1 plays a role in the regulation of gene expression during embryonic development, as well as participation in axial patterning and cellular proliferation and differentiation (Hildebrand and Soriano, 2002;Van Hateren et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other, less well-investigated, human diseases are beginning to see the groundwork being laid. Ribosomal DNA expression, rDNA loss, nucleolus-mediated stress responses, and heterochromatin defects are now being connected to neurological diseases (Jesse et al 2017;Maina et al 2018;Nunez Villacis et al 2018;Sun et al 2018) -whether these are confirmed, or are found to be consequential to the disease, remains to be seen.…”
Section: Disease Phenotypes -The Real and The Potentialmentioning
confidence: 99%
“…The regulation of this gene is complex; it has multiple isoforms and alternative promoters [30] and gene expression is regulated by a variety of stimuli, including cytokines, insulin, exercise and the cold [31]. PGC-1 α can induce ribosomal transcription under stress conditions such as oxidative stress and exercise [32].…”
Section: Discussionmentioning
confidence: 99%